Sum of Vague Ideals of Gamma Near-Ring - Bhaskar, L.; Nagaiah, T.; Narasimha Swamy, P.; Srinivas, T. (International Journal of Engineering and Technology, 2018)
In this paper, we introduce the concept of sum and direct sum of vague ideals of gamma near-ring and also discuss some related properties of vague ideals of gamma near-ring.Â Â